The Role of Poster Presentation in Facilitating English Listening Skills - Yuliani, Fitria (Melekliterasi Press, 2023)
This study aims to investigate the role of poster presentations in facilitating English listening skills in Indonesian EFL classrooms. The research problem revolves around the effectiveness of poster presentations as a teaching method for improving listening skills in English language learning. The qualitative inquiry method was utilized, involving observations and interviews with both students and teachers. This allowed for a deeper understanding of the impact of poster presentations on students' listening comprehension in the EFL context. The novelty of this study lies in its focus on poster presentations as a specific pedagogical tool for enhancing listening skills in a non-native English-speaking environment. This research contributes to the existing literature by providing insights into the potential of visual aids, such as posters, in improving English listening proficiency. The results of the study revealed that poster presentations can significantly contribute to the development of English listening skills among Indonesian EFL learners. The findings demonstrate the value of incorporating visual and auditory elements together in language learning activities, and highlight the potential of poster presentations as a valuable teaching strategy in EFL classrooms.